(untitled) - Abegg, Martin; Flint, Peter; Ulrich, Eugene (Edinburgh, 1999)
.AB: Three of the world's foremost dead sea scrolls scholars present the first english translation of the earliest biblical documents ever discovered
Keywords: Abegg, Martin; Flint, Peter; Dead Sea Scrolls